2018
DOI: 10.1002/jcb.27307
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Triptolide inhibits the proliferation and migration of medulloblastoma Daoy cells by upregulation of microRNA‐138

Abstract: Medulloblastoma is a primitive neuroectodermal-derived brain tumor and the most common malignant brain tumor in children. Triptolide (TPL) is the major active component extracted from Tripterygium wilfordii Hook F. This study aimed to explore the effects of TPL on medulloblastoma cell proliferation, migration, and apoptosis, as well as the underlying possible molecular mechanism. Viability, proliferation, and apoptosis of Daoy cells were measured using cell counting kit-8 assay, 5-bromo-2'-deoxyuridine incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Migration of MG63 and U2OS cells was measured using a two-chamber migration assay (Corning Incorporated, New York, NY) with 8 lm pore filters as earlier described [23]. The incubation time was 48 h. Migrated cells in the lower chamber were stained using 0.5% crystal violet solution (Beyotime Biotechnology) and counted under microscope (40Â, Nikon).…”
Section: Two-chamber Migration Assaymentioning
confidence: 99%
“…Migration of MG63 and U2OS cells was measured using a two-chamber migration assay (Corning Incorporated, New York, NY) with 8 lm pore filters as earlier described [23]. The incubation time was 48 h. Migrated cells in the lower chamber were stained using 0.5% crystal violet solution (Beyotime Biotechnology) and counted under microscope (40Â, Nikon).…”
Section: Two-chamber Migration Assaymentioning
confidence: 99%
“…These compounds include the CDK inhibitors palbociclib and alvocidib, the AMPK inhibitor dorsomorphin, the IKK inhibitor BMS‐345541, the smoothened receptor antagonist cyclopamine, the topoisomerase inhibitors topotecan and doxorubicin, the GABA receptor agonist ivermectin, the NF‐κB pathway inhibitor auranofin, the MTOR inhibitor dactolisib, the AKT inhibitors MK‐2206 and pyrvinium‐pamoate, the HMGCR inhibitor simvastatin, the HDAC inhibitors apicidin, vorinostat, and givinostat, and the DNA synthesis inhibitor anisomycin. In addition, the survivin inhibitor YM155 (Brun et al ., ), the AKT inhibitor pyrvinium (Li et al ., ), and the RNA polymerase inhibitor triptolide (Zhang et al ., ) have been shown to exert anticancer effects on MB cells, although there were no results regarding effects on MB stem cells. More importantly, the CMap analysis identified the PI3K inhibitor GDC‐0941, which has been demonstrated to target CD133‐positive stem cell‐like MB subpopulations (Ehrhardt et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, triptolide can also achieve anticancer effects by regulating microRNAs. Haifang Zhang et al found that triptolide can inhibit the PI3K/AKT and Notch pathways, thereby exerting an anticancer effect on medulloblastoma cells 39 . Similarly, studies have shown that triptolide can increase the expression of microRNA-181a, which participates in the proliferation, migration and apoptosis of SH-SY5Y cells, thereby exerting a tumor-suppressing effect 40 .…”
Section: Biological Functionsmentioning
confidence: 99%